Global profiling of DNA methylation erasure in mouse primordial germ cells - Guibert, Sylvain; Forné, Thierry; Weber, Michael

(untitled) (Genome Research, 2012)
Epigenetic reprogramming, characterized by loss of cytosine methylation and histone modifications, occurs during mammalian development in primordial germ cells (PGCs), yet the targets and kinetics of this process are poorly characterized. Here we provide a map of cytosine methylation on a large portion of the genome in developing male and female PGCs isolated from mouse embryos. We show that DNA methylation erasure is global and affects genes of various biological functions. We also reveal complex kinetics of demethylation that are initiated at most genes in early PGC precursors around embryonic day 8.0–9.0. In addition, besides intracisternal A-particles (IAPs), we identify rare LTR-ERV1 retroelements and single-copy sequences that resist global methylation erasure in PGCs as well as in preimplantation embryos. Our data provide important insights into the targets and dynamics of DNA methylation reprogramming in mammalian germ cells.